Spontaneous Ruptured Pyomyoma in a Nulligravid Female: A Case Report and Review of the Literature. (2nd July 2018) - Read, S.; Mullins, J.
Abstract : Introduction. Pyomyoma, or suppurative leiomyoma, is a rare complication of uterine fibroids. It occurs most commonly in the setting of pregnancy, the immediate postpartum period, or postmenopausal status. It may also arise after recent uterine instrumentation, after uterine artery embolization, or in immunocompromised patients. The most likely cause of pyomyoma is vascular compromise followed by bacterial seeding from direct, hematogenous, or lymphatic spread. Diagnosis is difficult, as the condition is rare, presents with vague symptoms, and is difficult to identify on imaging. Definitive diagnosis is only possible with surgery. Pathology shows a degenerating fibroid with hemorrhage, necrosis, cystic degeneration, and/or inflammatory change. Cultures of the pus contained within often show polymicrobial infection. Case Presentation. Our patient is a 24-year-old nulligravid female who presented with a surgical abdomen, fever, hypotension, and leukocytosis. She had no significant prior medical or surgical history, no history of uterine instrumentation, and no history of pelvic infection; she was not currently sexually active at the time of presentation. She was taken to the operating room, where she underwent diagnostic laparoscopy. This showed a ruptured pyomyoma originating in the left broad ligament. She then underwent laparoscopic myomectomy. She was transferred to the ICU intubated; she slowly recovered on IV antibiotics and was discharged home on postoperative day 10. Discussion. Pyomyoma is a rare condition and is even rarer in premenopausal patients without recent history of pregnancy or uterine instrumentation. This demonstrates an unusual case of spontaneous pyomyoma in the absence of risk factors, other than a history of known fibroids. Pyomyoma should be considered as a diagnosis in patients with sepsis, history of fibroids, and no other identifiable source of infection.